'For the trees have no tongues': eco-feedback, speech, and the silencing of nature. Issue 0 (December 2021) - Harvey, Matt; Vanderheiden, Steve
Abstract : When Christopher Stone argued for the extension of legal standing to natural objects, he proposed a guardianship model for representing the rights or interests of nonhuman nature. This approach requires that natural objects or systems be able to intelligibly communicate information regarding needs associated with their continued sustainable flourishing. Drawing upon both 'law beyond the human' approaches to legal theory and New Materialist theories about nonhuman subjectivity, we conceive of this mode of communication as a political speech act, albeit one that must be interpreted through eco-feedback collected in the study of natural systems rather than directly transmitted from speaker to listener. We then apply this conception of communication to human rights contexts in which efforts to distort or to otherwise manipulate this eco-feedback could be construed as an anti-democratic interference in speech rights, arguing for the extension of such rights to protect against such interference.